Does diffusion‐weighted imaging improve therapy response evaluation in patients with hepatocellular carcinoma after radioembolization? comparison of MRI using Gd‐EOB‐DTPA with and without DWI. Issue 3 (17th December 2014) - Schelhorn, Juliane; Best, Jan; Reinboldt, Marcus P.; Dechêne, Alexander; Gerken, Guido; Ruhlmann, Marcus; Lauenstein, Thomas C.; Antoch, Gerald; Kinner, Sonja
<x xml:space="preserve">Abstract</x> Purpose To investigate whether additional diffusion‐weighted imaging (DWI) improves therapy response evaluation by Gd‐EOB magnetic resonance imaging (MRI) in hepatocellular carcinoma (HCC) after radioembolization. Materials and Methods Fifty patients with radioembolization for HCC underwent gadobutrol and Gd‐EOB MRI with DWI prior to and 30, 90, and 180 days after radioembolization. A combination of gadobutrol MRI, alpha‐fetoprotein, and imaging follow‐up served as the reference standard. Two radiologists reviewed Gd‐EOB alone (Gd‐EOB), DWI alone (DWI), and the combination of both (Gd‐EOB+DWI) separately and in consensus using a 4‐point‐scale: 1 = definitely no tumor progression (TP), 2 = probably no TP, 3 = probably TP, 4 = definitely TP. Receiver operating characteristic (ROC) and kappa analysis were performed. Results Kappa values for Gd‐EOB, DWI, and Gd‐EOB+DWI ranged between 0.712 and 0.892 (P < 0.001). 30 days after radioembolization three out of 38 patients showed TP, which was missed by DWI in one case. No significant area under the curve (AUC) difference between Gd‐EOB (1.0, P = 0.004), DWI (0.881, P = 0.030), and Gd‐EOB+DWI (1.0, P = 0.004) was found (P = 0.320). 90 days after radioembolization six out of 28 patients showed TP, which was detected in one patient only by DWI and Gd‐EOB+DWI. The AUC did not differ significantly (P = 0.319) between Gd‐EOB (0.890, P = 0.004), DWI (1.0, P < 0.001), and Gd‐EOB+DWI (1.0, P < 0.001). 180 days after radioembolization five patients showed TP, which in one case was missed by DWI. The AUC did not differ significantly (P1 = 0.322, P2 = 0.369, P3 = 0.350) between Gd‐EOB (1.0, P = 0.003), DWI (0.913, P = 0.016), and Gd‐EOB+DWI (0.963, P = 0.007). Conclusion Additional DWI does not substantially improve therapy response evaluation by Gd‐EOB MRI in HCC after radioembolization but proved helpful in single cases. J. Magn. Reson. Imaging 2015;42:818–827.